Identification of a homozygous recessive variant in PTGS1 resulting in a congenital aspirin-like defect in platelet function - Chan, Melissa V.; Hayman, Melissa A.; Suthesh Sivapalaratnam; Marilena Crescente; Allan, Harriet E.; Edin, Matthew L.; Zeldin, Darryl C.; Milne, Ginger L.; Jonathan Stephens; Daniel Greene; Moghees Hanif; O'Donnell, Valerie B.; et al. (Haematologica (Roma), 2021)
We have identified a rare missense variant on chromosome 9, position 125145990 (GRCh37), in exon 8 in PTGS1 (the gene encoding cyclo-oxygenase 1, COX-1, the target of anti-thrombotic aspirin therapy). We report that in the homozygous state within a large consanguineous family this variant is associated with a bleeding phenotype and alterations in platelet reactivity and eicosanoid production. Western blotting and confocal imaging demonstrated that COX-1 was absent in the platelets of three family members homozygous for the PTGS1 variant but present in their leukocytes. Platelet reactivity, as assessed by aggregometry, lumi-aggregometry and flow cytometry, was impaired in homozygous family members, as were platelet adhesion and spreading. The productions of COX-derived eicosanoids by stimulated platelets were greatly reduced but there were no changes in the levels of urinary metabolites of COX-derived eicosanoids. The proband exhibited additional defects in platelet aggregation and spreading which may explain why her bleeding phenotype was slightly more severe than those of other homozygous affected relatives. This is the first demonstration in humans of the specific loss of platelet COX-1 activity and provides insight into its consequences for platelet function and eicosanoid metabolism. Notably despite the absence of thromboxane A2 (TXA2) formation by platelets, urinary TXA2 metabolites were in the normal range indicating these cannot be assumed as markers of in vivo platelet function. Results from this study are important benchmarks for the effects of aspirin upon platelet COX-1, platelet function and eicosanoid production as they define selective platelet COX-1 ablation within humans.